Detection of blaNDM, blaDIM, blaIMP, blaVIM and blaCTX-M-15 beta-lactamase Genes among Pseudomonas aeruginosa and Acinetobacter baumannii Strains Isolated from Two Hospitals of Tehran, Iran - Farajzadeh Alan, Tahere; Goudarzi, Hossein; Fallah, Fatemeh; Hashemi, Ali; Doustdar, Farahnoush; Bostan, Hojat (Novelty in Biomedicine, 2016)
Background: In this study, we evaluated the existence of blaNDM , blaDIM, blaIMP, blaVIM, blaCTX-M-15 beta-lactamase genes among Pseudomonas aeruginosa and Acinetobacter baumannii strains isolated from hospitalized patients. Materials and Methods: From June 2013 to May 2014, thirty-four nonduplicate nonconsecutive isolates of A. baumannii and P. aeruginosa were isolated from blood, respiratory tract, wound, sputum and urine samples of patients from hospitalized in two hospitals in Tehran, Iran. Antibiotic susceptibility test was performed by Kirby-Bauer disc diffusion method according to CLSI guidelines. In this study, the frequency of MBL (metallo-beta-lactamase) producers was evaluated by CDDT (Combined disk diffusion test) and prevalence of blaNDM, blaDIM, blaIMP, blaVIM and blaCTX-M-15 genes were evaluated by PCR and sequencing methods among P. aeruginosa and A. baumannii strains isolated from hospitalized patient of Tehran during 2013 -2014 years. Results: Of thirty-four non-fermenter isolates, 24 (70.58%) P. aeruginosa and 10 (29.41%) as A. baumannii were isolated and identified. High rate of resistance to common antibiotics were detected specially among A. baumannii isolates that showed 100% resistance to 4 of tested antibiotics. The CDDT results reveal that 4 (16.66%) of the P. aeruginosa isolates and 1 (10%) of the A.baumannii were positive for production of MBLs. The prevalence of blaCTX-M-15 gene among 10 A. baumannii isolates was 4 (40%), and for IMP-1, 2 (20%). The